2023
DOI: 10.3390/cells12081168
|View full text |Cite
|
Sign up to set email alerts
|

Down Syndrome Altered Cell Composition in Blood, Brain, and Buccal Swab Samples Profiled by DNA-Methylation-Based Cell-Type Deconvolution

Abstract: Down syndrome (DS) is a genetic disorder caused by an extra copy of chromosome 21 that presents developmental dysfunction and intellectual disability. To better understand the cellular changes associated with DS, we investigated the cell composition in blood, brain, and buccal swab samples from DS patients and controls using DNA methylation-based cell-type deconvolution. We used genome-scale DNA methylation data from Illumina HumanMethylation450k and HumanMethylationEPIC arrays to profile cell composition and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 56 publications
0
3
0
Order By: Relevance
“…EAA was observed in blood samples from populations with trisomy 21 (Horvath et al., 2015; Xu et al., 2022). At the same time, consistent decreases in naïve lymphocytes and increases in memory lymphocytes were observed in trisomy 21 patients (Zhang, Stolrow, et al., 2023). The direction of EAA and naïve and memory lymphocyte change suggest the immune cell composition's confounding effect on EAA in trisomy 21.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…EAA was observed in blood samples from populations with trisomy 21 (Horvath et al., 2015; Xu et al., 2022). At the same time, consistent decreases in naïve lymphocytes and increases in memory lymphocytes were observed in trisomy 21 patients (Zhang, Stolrow, et al., 2023). The direction of EAA and naïve and memory lymphocyte change suggest the immune cell composition's confounding effect on EAA in trisomy 21.…”
Section: Discussionmentioning
confidence: 54%
“…Specifically in human blood, our previous research employed differentially methylated regions identified between purified leukocyte subtypes to develop a reference‐based deconvolution algorithm, allowing estimation of the distribution of various leukocyte subtypes (Salas et al., 2022). This blood deconvolution approach has been utilized to investigate altered immune cell composition in multiple diseases, such as cancer (Chen et al., 2022, 2023), hypertension (Kresovich et al., 2023), and trisomy 21 (Zhang, Stolrow, et al., 2023).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, nRBC proportions were estimated from DNA methylation array data, rather than using actual cell counts, and cell-type deconvolution in individuals with DS may be confounded by the presence of blast cells that are common in DS and not accounted for in the analysis [ 17 ]. Cell composition deconvoluted from DNA methylation arrays has been previously reported to be altered in DS blood compared to non-DS blood [ 64 ]. Further, we previously reported a positive relationship between high nRBC proportions in newborns with DS and the presence of somatic GATA1 mutations, indicative of transient abnormal myelopoiesis (TAM) or silent TAM, and it is possible that the relationship between CHD and global hypomethylation in males may be confounded by this preleukemic condition [ 17 ].…”
Section: Discussionmentioning
confidence: 99%